2022
DOI: 10.1136/ejhpharm-2022-003304
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactam allergy in patients: an antibiotic stewardship challenge

Abstract: BackgroundPatients are commonly reported as being allergic to beta-lactam (BL) antibiotics. However, many patients with this reported allergy are able to receive BL treatments because they do not have true allergies. In many cases these are simply intolerances due to side effects reported as an allergy. Delabelling these patients leads to better clinical outcomes, optimal antibiotic usage, decreased bacterial resistance and reduced healthcare costs. Therefore, the aims of this study were to identify incorrectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…referred them to the allergy department for classic drug allergy assessment (ST and DPT). The authors reported efficacy data for 176 patients collected over 21 months that were similar to those reported for faster strategies [51] In our hospital [48], the strategy is aimed at assessing the tolerance of chosen ß-lactam through the antibiotic stewardship program. After discharge, the patient is referred to the allergy department to complete a classic study for drug allergy assessment.…”
Section: Unclear Risk 18mentioning
confidence: 81%
See 1 more Smart Citation
“…referred them to the allergy department for classic drug allergy assessment (ST and DPT). The authors reported efficacy data for 176 patients collected over 21 months that were similar to those reported for faster strategies [51] In our hospital [48], the strategy is aimed at assessing the tolerance of chosen ß-lactam through the antibiotic stewardship program. After discharge, the patient is referred to the allergy department to complete a classic study for drug allergy assessment.…”
Section: Unclear Risk 18mentioning
confidence: 81%
“…Other less resolutive strategies have been assayed to enable the use of some ß-lactam antibiotics in patients with a penicillin allergy label. In a hospital in Castellon, Spain [51], pharmacists identified admitted patients with a penicillin allergy label and Table 2. Specialties and Risk for a True Allergy in the Systematic Review of Powell et al [43].…”
Section: Strategies To Slow and Partially Delabel Penicillin Allergymentioning
confidence: 99%
“…Forty-six patients (44.6%) were not delabelled for not attending the scheduled study due to advanced age, comorbidities, death or from unknown causes, data similar to the Bodega-Azuara study. 8 De-labelling based on challenge with a single dose of amoxicillin or penicillin without previous skin tests can be useful in low-risk cases, although up to 3.43% of positive cases can be found. 9 In conclusion, our study shows that the integration of allergy into the ASP group in the Spanish context safely allowed a greater prescription of first-choice antibiotics (95.3%) in hospitalized patients with a diagnosis of infection and that it was possible to withdraw or modify the label of allergy to beta-lactams in 52.7% of cases.…”
Section: /120)mentioning
confidence: 99%